Case Report: The Parkes-Weber syndrome in the patient who underwent coronary surgery - Milosevic, Nemanja; Okiljevic, Bogdan; Micovic, Slobodan; Bojic, Milovan; Zivkovic, Igor (Frontiers in Cardiovascular Medicine, 2025)
Parkes-Weber Syndrome is a rare congenital vascular abnormality characterized by aneurismatic illness of blood arteries in the afflicted limb, as well as hypertrophy, ulceration, ischemia, and high-output heart failure. Imaging investigations are required to provide a diagnosis, with contrast arteriography being the gold standard. The majority of treatment options are endovascular, with surgical excision for arteriovenous malformations and limb amputation as alternatives. We describe a 73-year-old male patient with mainly asymptomatic PWS, coronary disease, and borderline EF (45%) who had CABG surgery. In individuals with established CAD and other cardiac disorders, it is critical to identify additional diseases or syndromes that might have a compounding effect on the heart, such as PWS and high-output heart failure.